Relating Mandates in the United States for Managing the Ocean to Ecosystem Goods and Services Demonstrates Broad but Varied Coverage - Foran, Christy M.; Link, Jason S.; Patrick, Wesley S.; Sharpe, Leah; Wood, Matthew D.; Linkov, Igor (Frontiers in Marine Science, 2016)
HIGHLIGHTS A complete catalog is presented of the legislative, executive and international mandates related to NOAA, as well as the subset of these relevant to NOAA-Fisheries. The ecosystem goods and services addressed by each NOAA mandate were assessed, as well as the overlap between the major mandates. The collective coverage across the suite of ecosystem goods and services is shown in comparison to the portfolio of mandates; differences in these profiles indicate a continued need for ecosystem-based management. There are numerous ecosystem goods and services (EGS) provided by the ocean. There are also multiple mandates to address this suite of EGS. What facets of the ocean EGS does this portfolio of mandates collectively address? How are these mandates interrelated? Are there gaps in their coverage of EGS? Are there areas of reinforcement? To elucidate this set of issues, we characterize the portfolio of mandates that a leading governmental ocean agency, the National Oceanographic and Atmospheric Administration (NOAA), and the subset of those that one of its Line Offices, the National Marine Fisheries Service (NOAA-Fisheries), is responsible for implementing. We link these mandates to a suite of EGS, evaluating the relative degree that each mandate addresses each EGS. The weighted overlap across mandates with respect to EGS was also estimated. Of the nearly 100 NOAA mandates, and the subset of 50 NOAA-Fisheries mandates, there was broad coverage of ocean EGS. Food production, habitat provision, genetic resources, recreation, tourism, historical and heritage value, and knowledge and science value were the EGS that had the highest degree of coverage. All EGS had at least some mandate coverage, although some had a limited number of mandates associated with them. There was some reinforcement across mandates, particularly for the top EGS, suggesting that the multiple facets of these EGS are being reasonably well addressed. The large number of mandates and the importance of EGS they address suggest that some form of coordination is warranted, particularly via adoption of an ecosystem-based approach to management.